Safety and Immunogenicity of Pertussis Vaccine Immunization during Pregnancy: A Meta-Analysis of Randomized Clinical Trials. (21st December 2022) - Simayi, Aidibai; Zhu, Liguo; Jin, Hui
Abstract : The objective of this meta-analysis is to assess the safety and immunogenicity of maternal pertussis vaccination based on randomized clinical trials. PubMed, Embase, Cochrane Library, Web of Science, China National Knowledge Internet, and Wan Fang Database were searched from inception up to the 8th of October 2021, using a protocol registered on PROSPERO with no. 42021287717, and a meta-analysis was conducted. We measured pooled geometric mean concentrations (GMCs) for IgG antibodies against pertussis and the incidence of serious adverse events (SAEs). We identified a total of 522 publications, and after a strict screening, we found that 6 RCTs were eligible for our meta-analysis. GMCs were determined with a standardized mean difference (SMD), and the pooled SMD of anti-PT, anti-FHA, and anti-PRN IgG from cord blood were 0.91 (95% CI: 0.58, 1.24), 1.03 (95% CI: (0.70, 1.35)), and 1.55(95% CI: 1.22, 1.88), respectively. The pooled OR of SAEs of women and infants did not show a statistical difference; the pooled ORs were 1.26 (95% CI: 0.78, 2.05); P = 0.35 ) and 0.61 (95% CI: 0.37, 1.01); p = 0.053 ), respectively. Infants of immunized women have significantly higher transplacental antibodies for protection against pertussis disease during the first 2 months of life.